A Gender-Based Analysis of Family Business Succession in the Entrepreneurship Study Program, Universitas Pendidikan Indonesia, Tasikmalaya Campus, Class of 2022 - Putri, Sezara Indah; Dinanti, Nadira; Hasanah, Hajar Sri; Fauziyah, Azizah (CV. Tripe Konsultan, 2025)
Succession in family business is a strategic process to ensure company sustainability through mature and considerate planning that takes into account family expectations, business interests, and successor readiness. In the past, men played a larger role in leadership, but now women also hold increasingly significant leadership positions. This shift reflects a change in how individual ability is viewed, no longer based solely on gender hierarchy, but on how an ideal and capable successor can bring positive change to the company. The research method used is a qualitative study with a descriptive approach. This research was conducted at the Universitas Pendidikan Indonesia (UPI), with the study object being family business founders and family business successor candidates who are students of the 2022 Entrepreneurship Study Program. The sampling method applied in this research is purposive sampling. The results show that the majority of family businesses have their own planning in selecting a successor by providing formal education and practical experience from an early age. Furthermore, 67% of family business owners do not consider gender as a determining factor in choosing a company successor. For them, mental readiness and commitment to running the business are the main requirements for a family business successor.